Twelve-Year Incidence of Open-angle Glaucoma: The Thessaloniki Eye Study. Issue 9 (15th September 2021) - Founti, Panayiota; Coleman, Anne L.; Wilson, M. Roy; Yu, Fei; Harris, Alon; Pappas, Theofanis; Anastasopoulos, Eleftherios; Koskosas, Archimidis; Salonikiou, Angeliki; Keskini, Christina; Malamas, Angelakis; Kilintzis, Vassilis; et al.
Abstract : Objective: The objective of this study was to determine the 12-year incidence of open-angle glaucoma (OAG), with further classification into primary open-angle glaucoma (POAG) and pseudoexfoliative glaucoma (PEXG), in an elderly White population. Design: A longitudinal, population-based study in urban Northern Greece. Participant: Surviving cohort of the 2554 Thessaloniki Eye Study subjects 60 years and above who had the baseline examination. Methods: The surviving cohort was re-examined 12 years after baseline, using the same methodology and the same standard operating procedures as in the baseline examination. The definitions of glaucoma and pseudoexfoliation were consistent throughout the study. The 12-year incidences of OAG, POAG, and PEXG with corresponding 95% confidence intervals (CIs) were calculated for the whole study population, consisting of clinic-visit and home-visit participants. The population at risk was defined as those who did not meet the study criteria for the diagnosis of glaucoma in either eye at baseline. Main Outcome Measures: Twelve-year incidence of OAG, with further classification into POAG and PEXG. Results: Of 1468 eligible subjects in the surviving cohort, 1092 were examined (participation rate 74%). Mean age at baseline was 68.9±4.6 years. Mean follow-up time was 11.6±1.6 years. The 12-year incidence of OAG was 4.4% (95% CI: 3.3-5.8); 0.37% per year. In the overall population the incidence of POAG and PEXG was 2.1% (95% CI: 1.3-3.2) and 2.3% (95% CI: 1.5-3.4), respectively. The corresponding incidence proportions were 2.9 (95% CI: 1.8-4.3) in those without PEX and 8.9 (95% CI: 5.8-12.9) in those with PEX at baseline and/or incidence. The latter was strongly associated with higher odds for incident glaucoma (odds ratio=3.34, 95% CI: 1.83-6.08, P <0.001). Of all incident OAG cases, 11.1% (95% CI: 4.4-24) had baseline intraocular pressure >21 mm Hg. Conclusions: The incidence of OAG was similar or higher compared with other White populations. The incidence of glaucoma in those with PEX was higher compared with the incidence of glaucoma in those without PEX.